Possible Application of Hydrocolloid Edible Coating Layer to Enhance the Quality of Fried Lotus Rhizome: Life Sciences-Biotechnology for prospective medical science - Minh Phuoc Nguyen (International Journal of Life Science and Pharma Research, 2022)
There is an increasing demand for healthier and functional products. Lotus (Nelumbonucifera) rhizome is as a case in point. It’s well naturally adapted in swamp regions as one of major crops in Mekong delta, Vietnam. It is rich in carbohydrates, essential minerals, soluble fibers, antioxidants, phytochemical constituents such as polyphenolics and oligomeric procyanidines. It’s extensively utilized as a traditional herbal medicine due to its strong antioxidant effect. Very small portion of total lotus rhizome cultivation undergo industrial processing. The processing of lotus parts into value added products must be encouraged to improve the market efficiency, generating employment for local laborers and accelerating income for rural farmers. During frying, oil absorption leads to negative effects in its flavour, odour and general organoleptic properties. The aim of this research was to investigate the in? uence of various hydrocolloids such as carrageenan, carboxymethyl cellulose, sodium alginate as edible coating layer to enhance the quality of fried lotus rhizome with respect to moisture reduction, oil uptake and overall acceptance. Different edible coating substances such as carrageenan, carboxymethyl cellulose, alginate in different concentrations (0.75%, 1.0%, 1.25%, 1.5% w/v) were examined on the lotus rhizome before frying at 190oC for 2.5 minutes in sunflower oil. Our results revealed that 1.25% carboxymethyl cellulose was appropriate for coating of the lotus rhizome. From this investigation it was hoped that, the functional and economic values of lotus rhizome would be enhanced.